Feeding habits of sardine (Sardinops sagax) in relation to their spawning activities - Mashifane_TB (Department of Oceanography, 2023)
Feeding activity of sardine (Sardinops sagax) from St Helena Bay and Gans Bay in the Southern Benguela was studied between February and April 2011 and related to reproduction. Feeding intensity of 373 sardine was calculated and correlated with caudal length across different gonad maturity and fat stages. Feeding intensity tended to be higher in small than large sardine (r = -0.14, n = 373, p = 0.005) and similar for both sexes (t = 1.567, df = 371, p = 0.12). Feeding intensity was high in St Helena Bay, possibly because of food availability. Gonad maturity and GSI were highest in February and were greater in St Helena Bay than in Gans Bay. Fat staging and the relative weight index were used to represent fish condition. Fat reserves varied, being low in February during the spawning season and peaking thereafter in March and April. A GLM indicated that feeding intensity in sardine was affected by time of year and gonad maturity state. Sardine fed throughout the study period but feeding intensity was highest in periods before- and after- spawning. With the observed continuous feeding and the accumulation of fat reserves before spawning, it appears S. sagax in the Southern Benguela employs both capital and income breeding strategies.